2003
DOI: 10.1111/j.1745-4565.2003.tb00362.x
|View full text |Cite
|
Sign up to set email alerts
|

THE OCCURRENCE, HEMOLYTIC ACTIVITY AND ANTIBIOTIC SUSCEPTIBILITY OF MOTILE AEROMONAS SPP. ISOLATED FROM MEAT AND MILK SAMPLES IN TURKEY

Abstract: Research was carried out to detect the incidence of motile Aeromonas species (A. hydrophila, A. caviae, A. sobria) in a variety of raw meat products (minced meat and chicken) and milk samples (raw andpasteurized) commonly consumed in Ankara. Motile Aeromonas species were isolated from 51.8% of samples detected; these were 40 (67.7%) of the 59 samples of minced meat, 20 (86.9%) of the 23 samples of chicken, 75 (47.7%) of the 157 samples of raw milk and 5 (16.0%) of the 31 samples of pasteurized milk. The domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(33 reference statements)
2
8
0
1
Order By: Relevance
“…When we done the sensitivity test for different antibiotics we saw that our isolates have multiple drug resistant (100 %) to cloxacillin , ampicillin , bacitracin , and penicillin and were resistant to oxytetracycline 56.5% (n=22/39) , tetracycline 33.4% (n=13/39), cephoxetin 30.8% (n=12/39), chloramphinicol and kanamycin 28.2% (n=11/39), streptomycin 23.1% (n=9/39), rifampicin 15.4% (n=6/39) which agree with the results of Vivekanandhan (15) and Zheng (27) , while Hassan (28) found the isolates from fish were resistant to (amoxicillin, meropenem , oral cephalosporin , cefaclor, cephalexin , cephalothin , colistin) , Gold and Salit(29) found the resistance was to pencillin , ampicillin , flucloxacillin, carbencillin , cefuzolin , Abdel-Gwad and Abdel-Rahman (30) found in vitro susceptibility of the Aeromonas hydrophila isolates to a variety of antibiotics revealed to 100% of isolates were resistant to penicillin and ampicillin , Soliman(31) all isolates were resistant to (ampicillin, and novobiocin)the similar results recorded by Sohair and Eman (32) who reported that isolates were resistant to (penicillin ,ampicillin) , Kaskhedikar and Chhabra (14) show 100% of isolates were resistant to (ampicillin and colistin ) antibiotics . also Yucel &Ctak (16), Emekdas(17) Soliman (33) , Chardrakanthi (34) , reported that all isolates were 100% resistant to (penicillin and colistin ). All these resurges found the same resistant that it is may be due to the β-lactamase enzyme production of these isolates, so they agree with the results of our study which show 100% resistance to Cloxacillin , penicillin and ampicillin antibiotics , and from this results we find that these isolates have multiple drug resistance and we agree in this with Vivekanandhan (15) and Zheng (27) .…”
Section: Discussionmentioning
confidence: 94%
“…When we done the sensitivity test for different antibiotics we saw that our isolates have multiple drug resistant (100 %) to cloxacillin , ampicillin , bacitracin , and penicillin and were resistant to oxytetracycline 56.5% (n=22/39) , tetracycline 33.4% (n=13/39), cephoxetin 30.8% (n=12/39), chloramphinicol and kanamycin 28.2% (n=11/39), streptomycin 23.1% (n=9/39), rifampicin 15.4% (n=6/39) which agree with the results of Vivekanandhan (15) and Zheng (27) , while Hassan (28) found the isolates from fish were resistant to (amoxicillin, meropenem , oral cephalosporin , cefaclor, cephalexin , cephalothin , colistin) , Gold and Salit(29) found the resistance was to pencillin , ampicillin , flucloxacillin, carbencillin , cefuzolin , Abdel-Gwad and Abdel-Rahman (30) found in vitro susceptibility of the Aeromonas hydrophila isolates to a variety of antibiotics revealed to 100% of isolates were resistant to penicillin and ampicillin , Soliman(31) all isolates were resistant to (ampicillin, and novobiocin)the similar results recorded by Sohair and Eman (32) who reported that isolates were resistant to (penicillin ,ampicillin) , Kaskhedikar and Chhabra (14) show 100% of isolates were resistant to (ampicillin and colistin ) antibiotics . also Yucel &Ctak (16), Emekdas(17) Soliman (33) , Chardrakanthi (34) , reported that all isolates were 100% resistant to (penicillin and colistin ). All these resurges found the same resistant that it is may be due to the β-lactamase enzyme production of these isolates, so they agree with the results of our study which show 100% resistance to Cloxacillin , penicillin and ampicillin antibiotics , and from this results we find that these isolates have multiple drug resistance and we agree in this with Vivekanandhan (15) and Zheng (27) .…”
Section: Discussionmentioning
confidence: 94%
“…from poultry sources compared to our findings have also been documented in previous study. Yucel and Citak (2003) detected motile aeromonads in 87% of poultry meat samples with predominance of Aeromonas hydrophila and Aeromonas sobria strains. Some other studies on chicken samples performed by Yucel and Erdem (2004), Sarımehmetoglu and Kuplulu ( 2001) and Hanninen (1993) had found a higher contamination levels of 86.95%, 82.9% and 93% with Aeromonas spp.…”
Section: Occurrence Of Aeromonas Hydrophilamentioning
confidence: 98%
“…Tous les échantillons étaient fortement contaminés par des bactéries : 66,6 %, 25,9 %, 29,6 %, 20,3 % et 12,9 % des échantillons crus étaient contaminés par Escherichia coli, Aeromonas spp., Staphylococcus aureus, E. coli 0157:H7 entérohémorragique et des salmonelles, respectivement. En outre, 10,9 %, 3,1 %, 4,68 %, 3 4 10 × 3.4 4 10 × 3.2 * 4 10 × 2.0 * 4 10 × 4.1 * 4 10 × 3.7 * ‫األعىل‬ ‫احلد‬ 5 10 × 1.5 4 10 × 8.9 4 10 × 4.9 5 10 × 1.5 4 ‫األعىل‬ ‫احلد‬ 5 10 × 1.1 3 10 × 4.6 4 10 × 1.1 5 10 × 1.1 5…”
Section: éTude Microbiologique De Burgers De Poulet éPicés Dans La VIunclassified